Mixed rearing correlates with the existence of Trichophyton verrucosum pathogens in humans - Wael F. El-Tras; Ahmed A. Tayel; Radi A. Mohamed; Doaa M. El-Kordy; Nevein N. El-Kady; Ahmed Samir (Wolters Kluwer Medknow Publications, 2015)
Background/Objective: Trichophyton verrucosum is a serious zoophilic dermatophyte causing dermatophytic infections and skin lesions in humans and animals. Raising small ruminants beside cattle is a common practice in rural areas of Egypt. Therefore, the current study emphasizes the risk of T. verrucosum spreading through backyard farming, recognizing the interconnectedness of ruminants and humans. Methods: A total of 478 cattle, 215 sheep, 186 goats, and 250 human contacts were investigated for the presence of skin lesions, and then the lesions were sampled. All samples were examined by fungal cultures using Sabouraud dextrose agar. Results: The highest rate of T. verrucosum isolates was recorded in cattle that grew up along with sheep and goats (14.5%), whereas the lowest rate was observed in cattle reared as a single species (6.6%), with a significant difference of p = 0.04, odds ratio = 2.42 at a 95% confidence interval: 1.03-5.65. In addition, there was a borderline significant difference of p = 0.05 between the presence of T. verrucosum pathogens in humans in contact with combined species of cattle, sheep, and goats (13.8%) and those in humans in contact with cattle only (3.3%); the odds ratio was 4.66 at a 95% confidence interval: 1.00-22.53. Moreover, the highest rate of T. verrucosum isolates in cattle was recorded in young cattle (calves). Tinea barbae was found in 11 human cases, while tinea corporis was determined in seven cases. Conclusion: Rearing different species of small ruminants with cattle supports the spread of T. verrucosum pathogens. Tinea barbae caused by T. verrucosum was predominant in the examined humans.